When a Social Experimenter Overwrites Effects of Salient Objects in an Individual Go/No-Go Simon Task – An ERP Study - Michel, René; Bölte, Jens; Liepelt, Roman (Frontiers in Psychology, 2018)
When two persons share a Simon task, a joint Simon effect occurs. The task co-representation account assumes that the joint Simon effect is the product of vicarious representation of the co-actor’s task. In contrast, recent studies show that even (non-human) event-producing objects could elicit a Simon effect in an individual go/no-go Simon task arguing in favor of the referential coding account. For the human-induced Simon effect, a modulation of the P300 component in Electroencephalography (EEG) is typically considered as a neural indicator of the joint Simon effect and task co-representation. Showing that the object-induced Simon effects also modulates the P300 would lead to a re-evaluation of the interpretation of the P300 in individual go/no-go and joint Simon task contexts. To do so, the present study conceptually replicated Experiment 1 from Dolk, Hommel, Prinz and Liepelt (2013) adding EEG recordings and an experimenter controlling the EEG computer to test whether a modulation of the P300 can also be elicited by adding a Japanese waving cat to the task context. Subjects performed an individual go/no-go Simon task with or without a cat placed next to them. Results show an overall Simon effect regardless of the cat’s presence and no modulatory influence of the cat on the P300 (Experiment 1), even when conceivably interfering context factors are diminished (Experiment 2). These findings may suggest that the presence of a spatially aligned experimenter in the laboratory may produce an overall Simon effect overwriting a possible modulation of the Japanese waving cat.